Acts - Parsons, Mikeal Carl, 1957- (Grand Rapids, Mich. : Baker Academic, 2008)
In Acts, one of eighteen volumes in the Paideia commentary series, leading biblical scholar Mikeal Parsons gleans fresh theological insight into Acts by attending carefully to the cultural and educational context from which it emerges. Parsons see Acts as a charter document explaining and legitimating Christian identity for a general audience of early Christians living in the ancient Mediterranean world. Graduate and seminary students, professors, and pastors will benefit from this readable commentary, as will theological libraries. - Publisher.
Introduction -- Part 1: Acts 1-7, the sense of a beginning -- Acts 1, the beginning of the church -- Acts 2, the miracle and meaning of Pentecost -- Acts 3:1-4:31, the healing of a lame man -- Acts 4:32-5:42, tensions within and without -- Acts 6-7, Stephen and the seven -- Part 2: Acts 8-12, beyond Jerusalem : Philip, Saul, Peter, and others -- Acts 8, Philip : a man on a mission -- Acts 9:1-31, Saul and Ananias : conversion and call -- Acts 9:32-11:18, Peter : his words and deeds -- Acts 11:19-12:25, Barnabas, Peter, and Herod -- Part 3: Acts 13-19, Paul's mission to the gentile world -- Acts 13-14, Paul's initial missionary campaign -- Acts 15:1-16:5, the Jerusalem Conference -- Acts 16:6-17:15, Paul in Macedonia -- Acts 17:16-18:17, Paul in Achaia -- Acts 18:18-19:41, Paul in Ephesus -- Part 4: Acts 20/28, Paul's farewell journey -- Acts 20:1-21:16, Paul's last journey to Jerusalem -- Acts 21:17-23:35, Paul in Jerusalem -- Acts 24-26, Paul before Felix, Festus, and Agrippa -- Acts 27-28, the sea voyage to Rome.
Formerly CIP.
Includes bibliographical references (p. 371-393) and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries; Bible; Bible -- N.T -- Acts -- Commentaries; Commentaries